2012
DOI: 10.2174/1876822901205010001
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Modulation of Immune-Associated Genes in LNCaP Prostate Cancer Cell Line

Abstract: Abstract:Background: Prostate cancer is the most common form of non-dermatologic cancer and the second leading cause of cancer deaths in the United States. Survival rate for the advanced disease still remains low, so current research is aimed at alternative or adjuvant treatments that will target components of the signal pathways in the progression of carcinogenesis with little or no cytotoxicity. In this study we investigated the effect of genistein on expression levels of genes involved in the immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“… 4 Thus, therapy with immune-associated genes shows great potential advantages in the treatment of cancer. 5 , 6 Both interferon-β (IFN-β) and interleukin-2 (IL-2) are important cytokines and play multiple roles in host immune system. They are also shown to display remarkable antitumor potential.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Thus, therapy with immune-associated genes shows great potential advantages in the treatment of cancer. 5 , 6 Both interferon-β (IFN-β) and interleukin-2 (IL-2) are important cytokines and play multiple roles in host immune system. They are also shown to display remarkable antitumor potential.…”
Section: Introductionmentioning
confidence: 99%
“…Genistein has been reported to induce cytotoxicity, inhibit cellular proliferation, and promote apoptotic cell death in various cancer cells in vivo and in vitro [11,12]. The anti-cancer effects of genistein has been demonstrated in many human cancers such as breast, lung, prostate, lymphoma, leukemia, and head and neck cancers [11,13] through many mechanisms that include: the inhibition of topoisomerase I & II [14], inhibition of telomerase activity [15], inhibition of tyrosine kinase signaling pathway, inhibition of cell survival proteins; Akt and NF-kβ [16] and anti-apoptotic proteins -Bcl-2 and Bcl-XL [17][18][19], and also the inhibition of angiogenesis [10]. Genistein has been shown to also display bipolar properties in which at low concentrations, it behaves as an antioxidant and at high concentration acts as a pro-oxidant [12].…”
Section: Introductionmentioning
confidence: 99%
“…Even though anti-cancer drugs usually target tumor cells by inducing apoptosis, it has been demonstrated that most tumors are resistant to chemotherapy-induced apoptosis (23). Thus recent studies have focused on using new therapeutic agents -nutraceutical phytochemicals such as genistein, in particular -which have significantly lower cytotoxicity compared to chemotherapy medicines but still exhibit anti-cancer effects (9).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of conducting extensive investigations into cancer and having considerable knowledge about its genomic basis, cancer still remains a serious threat to human life (9). Current protocols for treatment of the cancers rely on the use of synthetic and chemical drugs; due to their unpleasant side effects, however, recent studies have been mainly focusing on the use of natural products and herbal plant-derived medicines.…”
Section: Introductionmentioning
confidence: 99%